Mapping the economic potential of MSMEs to develop the BUMDes business - Ardiyan Saptawan; Junaidi Junaidi; Ermanovida Ermanovida; Retno Susilowati (Community Empowerment, 2022)
The main objective of this program is to identify Lorok Village's economic potential and to educate the target audience about the design of the BUMDes business development strategy for maximizing Lorok Village's economic potential. This program was attended by eleven BUMDes administrators from Lorok Village, Kabal Island, Tanjung Pule, and Payakabung, as well as ten Lorok Village officials. Counseling about mapping Lorok Village's economic potential and organizing a network of cooperation and marketing as a management strategy, as well as question and answer activities, is the method used. As a result of this program, BUMDes business managers are better able to understand the economic potential of Lorok Village and gain a better understanding of BUMDes business development strategies.